Effect of Different Feeder Designs on the Development of Osmanabadi Goat Kids - Kankarwal, Gaurav; Pathak, Rupal; Bhagat, Vandana; Singh, Nishma; Doneria, Raina; Parmar, Mehtab S.; Kanwar, Kanti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The effect of feeder design on the growth performance of the Osmanabadi goat kids was investigated at the Seed Centre for Osmanabadi Goats-DRS Farm, Dau Shri Vasudev Chandrakar Kamdhenu Vishwavidyalaya, Durg, (CG, India) for a period of 60 days during the winter season. A total of 18 Osmanabadi weaned kids were randomly divided into three groups with six kids (3 males and 3 females) in each group viz T1, T2 and T3. T1 group kids (control) were kept on conventional feeder, T2 on circular feeder and T3 on linear feeder. The maximum (P>0.05) mean body weight was observed on the 60th day in T3 (13.23±0.33), as compared to T2 followed by T1. Similarly, a significantly higher mean body length was observed in T3 as compared to T1 and T2 groups on 45th and 60th day of the study. The maximum mean heart girth was observed on the 60th day in T3 (57.5±0.67) followed by T2 (55.3±1.4). Furthermore, the maximum mean height at wither was observed on the 60th day in T3 (58.1 ± 0.7) than T2 (57.1 ± 0.7) and T1 (55.8 ± 1.7). Our results revealed that modified linear feeder design positively influenced the growth performance of goat kids.